¡Obtuve la entrevista! ¿Cómo se codifica para visibilizar los conceptos? - Lopez Hernandez, Rosa Eva (Emerging Trends in Education, 2020)
Reseña de llibro Saldaña, J. (2016). The Coding Manual for Qualitative Researchers (3a. Ed). London, U.K: Sage.